2017
DOI: 10.1108/jic-11-2016-0112
|View full text |Cite
|
Sign up to set email alerts
|

Competitiveness and disclosure of intellectual capital: an empirical research in Portuguese banks

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 60 publications
(80 reference statements)
3
75
0
1
Order By: Relevance
“…Our study confirms first that the level of the disclosure of intangible assets is not high for Spanish financial institutions, which is in line with previous findings. Likewise, Ferreira et al (2017) found a global index in the annual report of 36.93% and of 28.60% in corporative websites. Likewise, Munthopa (2013) found an intellectual capital disclosure index of 32%, corresponding to 40% for internal capital category, 32% for external capital, and the rest 28% for human capital.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Our study confirms first that the level of the disclosure of intangible assets is not high for Spanish financial institutions, which is in line with previous findings. Likewise, Ferreira et al (2017) found a global index in the annual report of 36.93% and of 28.60% in corporative websites. Likewise, Munthopa (2013) found an intellectual capital disclosure index of 32%, corresponding to 40% for internal capital category, 32% for external capital, and the rest 28% for human capital.…”
Section: Discussionmentioning
confidence: 95%
“…4). Continuing the important line of work that has already been started by classical authors such as Williams (2001) and, more recently, by authors such as Ferreira et al (2017), in Table1 it has been incorporated the most relevant aspects of this topic.…”
Section: Literature Review: the Intangibles Indexesmentioning
confidence: 99%
See 3 more Smart Citations